An 8mW ultra low power 60GHz direct-conversion receiver with 55dB gain and 4.9dB noise figure in 65nm CMOS - Shang, Yang (2013)
An ultra low power direct-conversion receiver is demonstrated for V-band 60GHz applications in 65nm CMOS process. The power consumption is significantly reduced by the design of low-power low noise amplifier (LNA), transconductance mixer and variable gain amplifier (VGA). A compact quadrature-hybrid coupler is developed for transconductance mixer for the reduction of both power and area. The proposed receiver (0.34mm2 chip area) is measured with 8mW power, the minimum single-side-band (SSB) noise figure (NF) of 4.9dB, and the maximum power conversion gain of 55dB.